Perencanaan Sumberdaya Manusia Untuk Mencapai Keunggulan Bersaing Perusahaan - Assery, Syeh; Tjahjono, Heru Kurnianto; Palupi, Majang (Jurnal Manajemen Bisnis, 2015)
This paper aims to explain  the conceptual aspects and the critical role of human resource management. One aspect of HRM is HR Planning. In relation to Strategic Management, it can be proposed that competitive advantage of a company can be achieved through a good human resource planning. This paper furthermore becomes a foundation on bridging theory between Human Resource Management and Strategic Management.